Knowledge and Practice of Personal Finance of Non-Teaching Staff in a Private University in Cebu City - POLINAR, MARK ANTHONY; Rico , Madelline; Celada, Jennibeth (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The purpose of the study is to examine the degree of knowledge and practice of personal finance of the non-teaching staff at a private university and to determine if the degree of knowledge of the respondents in terms of the variables under personal finance has a significant relationship to the degree of practice. The formulated questions were addressed using a descriptive-correlational approach. Fifty (50) non-teaching staff were chosen to participate in the data collection using simple random sampling and then examined the gathered data using the weighted mean and Pearson correlation coefficient. The study’s findings showed that the non-teaching staff who participated have a modest knowledge and practice of the indicators considered under personal finance. On the one hand, the study revealed that the degree of knowledge and practice of budgeting, saving, spending, insurance, and investment correlate, resulting in rejecting the null hypothesis. On the other hand, the degree of knowledge and practice of emergency fund and debt management showed no correlation that led the researchers not to reject the null hypothesis. The researchers concluded that non-teaching staff generally have sufficient understanding and execution of budgeting, saving, spending, emergency fund, debt management, insurance, and investment, yet in terms of the degree of the practice of setting emergency funds and investing money, have both obtain poor responses. Furthermore, recommendations and an action plan were provided to help them achieve financial robustness.